A new technique of flexor carpi ulnaris transfer in multilevel surgery for upper extremity deformities in spastic cerebral palsy - Georgy Chibirov; Mairbek Pliev; Dmitry Popkov (Medicinski glasnik, 2020)
Aim: To assess treatment outcomes of cerebral palsy (CP) patients who underwent upper limb surgical treatment including new technique of flexor carpi ulnaris (FCU) transfer. Methods: The study included an outcome of orthopaedic surgeries in 30 upper limbs of 25 CP patients aged 10 to 24 years (mean age of 15.1 years). In addition to standard orthopaedic assessment, we used the integral scales of the Gross Motor Function Classification System (GMFCS) and Manual Ability Classification System (MACS). Functional disorders of the upper limb were also evaluated with classifications of Van Heest, House, Gshwind and Tonkin. Results: A total of 30 surgical interventions were performed. In seven patients with hemiparesis, surgical treatment was accompanied by simultaneous intervention on the lower limb. Improvement of the functional capabilities and cosmetic appearance was noted in all cases in a follow-up over 12 months, as evidenced by an improvement in the functional class according to Van Heest classification. Conclusion: A new technique of FCU transfer to the radius showed to be an effective method to address pronation contracture of the forearm joints and can be used in combination with other elements of surgical intervention for elbow and thumb contractures. The FCU rerouting and transfer to distal radius is a good option in the absence of active supination. Distal release of FCU weakening flexion forces with a simultaneous procedure restoring active wrist extension provides satisfactory outcomes in the treatment of associated flexed wrist contracture.
Keywords: cerebral palsy; flexor carpi ulnaris transfer; pronation contracture